Economic literacy among students in Malaysia - Nurul Fazira Muhamad Nizam; Lai, Wei Sieng; Noorasiah Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2020)
Basic knowledge of economy is very important for all community levels regardless of their academic backgrounds. Measuring the economic literacy level among students in Malaysia is important as a benchmark to improve students’ economic literacy. The purpose of this study is to identify the level of economic literacy among students in Malaysia. The data used in this study were collected through surveys. The questions in this economic literacy test were composed according to Malaysia's own references and added with some demographic information of the respondents. 400 samples were randomly taken from students which come from different learning institutions and backgrounds in Malaysia. Next, this data is analyzed using Tobit regression model. Sigma value in this study is used to determine whether this is a good model or not. Dependent variable used in this study are the scores in economic literacy tests, while independent variables are gender, ethnicity, household income, residential location and field of study. The result of this study found that students in all type of education has low level of economic literacy. The household income and the field of study was significant and had influence on the level of economic literacy among students.